InterCom (1954) - Office of Public Relations. Duke University Medical Center (1954)
Volume 1, numbers 1-2, 4, and 6; February 1954; April 1954; August 1954; December 1954. Published bimonthly by Duke Hospital and the Duke Hospital Women's Auxiliary for Duke Hospital employees, staff, students, and volunteers. Mrs. Earl Porter,Editor; Wendell Weisend, Advisor.